Prevalence, Pathogenicity and Physiological Studies of Cercospora tageticola Ellis and Everhart Causing Leaf Spot in Marigold - Gupta, S.; Chandel, S. (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken during first week of October to second week of October for two consecutive years i.e. 2017 and 2018 at Dr. YSP University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh (173 230), India.The objective of the investigation was to find out the prevalence of of Cercospora tageticola through morphological analysis, pathogenicity and physiological studies for developing future control strategies. Highest disease incidence and severity (62.4% and 70.4%) was recorded in Nauni while, least incidence was observed in Chhogtali (8.9% and 8.6%) of Sirmaur district. The disease exhibited characteristic symptoms, starting as circular to angular, dark reddish brown or purplish spots that turned almost brown black, the centre of which is often greyish in colour. On advancement, symptoms slowly develop from lower to upper leaves giving blighted appearance. Flowers displayed small but noticeable light to dark brown lesions as they grow, initially circular and later becoming unequal to irregular blotches. Morphological analysis of the test pathogen revealed hyaline, septate and branched mycelia (8.54-11.34 mm2) in older cultures. The pathogen produced geniculate conidiophores (3.5-6×50-300mm) with hyaline conidia (2.7-5×70-200 mm2). The identified pathogen was Cercospora tageticola. Koch’s postulates confirmed its pathogenicity on “Pusa Narangi Gainda” variety, with symptoms appearing 8 days after inoculation, indicating a 192-hour incubation period. Cultural and physiological factors such as Carrot decoction agar as the optimal medium, 25°C as the temperature and pH 5.5 for maximum radial growth and dry mycelial weight significantly influenced pathogen growth in vitro, with black to greyish mycelial growth displaying good sporulation.